Research on Micro-/Nano-Positioning System Driven by a Stepper Motor - Minjie Liu; Yangyang Yu; Liangyu Cui; Ning Ji; Xiaofan Deng (Actuators, 2024)
To achieve cost-effective micro-/nano-displacement adjustment, this paper integrates the advantages of flexible hinge micro-/nano-displacement transmission. A linear stepper motor is utilized as the driving component to design and develop a high-precision, low-cost micro-/nano-positioning system. The structure, design, and working principles of the micro-/nano-positioning platform are introduced. The scaling factor model between micro-positioning platforms and nano-positioning platforms is analyzed. Static and dynamic models of flexible mechanisms have been established. The dimensions of the mechanical structure and the selection of motors are determined. The mechanical characteristics of the micro-/nano-positioning platform are validated through finite element analysis. To address the characteristic of increasing loads during the transmission process, an intelligent control system based on current feedback is designed and developed. The integration of drive and control provides a high level of system integration. Finally, experimental calibration was conducted to test the motion characteristics of the linear stepper motor-driven micro-/nano-positioning platform. It achieved a minimum displacement control resolution of 100 nm and demonstrated a certain level of stability.